2011
DOI: 10.1002/lt.22449
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation in human immunodeficiency virus-infected patients: Procoagulant, but is antithrombotic prophylaxis required?

Abstract: Liver transplantation (LT) for human immunodeficiency virus (HIV)-positive recipients with end-stage liver disease has become an accepted practice. However, because these patients are increasingly being recognized as prothrombotic, we reviewed their posttransplant thrombotic complications. Because morphological changes might be responsible in part for this prothrombotic state, we also conducted a histopathological review of explants from HIV-positive patients. Between 1990 and 2010, 24 of 3502 recipients (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
2
16
2
Order By: Relevance
“…Other studies have reported thrombotic complications such as arterial thrombosis as a significant problem in LT in HIV-1 infected patients [23]. However, in our study, we did not experience this complication.…”
Section: Discussioncontrasting
confidence: 79%
“…Other studies have reported thrombotic complications such as arterial thrombosis as a significant problem in LT in HIV-1 infected patients [23]. However, in our study, we did not experience this complication.…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to our series, 1 they observed no cases of hepatic artery thrombosis (HAT) among 32 HIV-positive liver transplant recipients. Vascular complications included 2 early hepatic artery stenoses (within 30 days) successfully treated by percutaneous transluminal angioplasty and stenting, 1 early portal vein thrombosis (day þ1) successfully treated by surgical thrombectomy, and 1 late hepatic vein stenosis (6 months after transplantation) successfully treated by percutaneous transluminal angioplasty and stenting; the overall incidence was 12.5%.…”
contrasting
confidence: 45%
“…As HIV infection is associated with a pro-thrombotic state, concerns have been raised regarding an increased risk of vascular complications post transplantation (52). Recent data from our Institution demonstrated an increased an increased incidence of hepatic artery thrombosis compared to HIV negative patients (12% vs. 3.2%, p=0.016) (53). Given the increased pro-thrombotic risk, the introduction of prophylactic subcutaneous heparin (5000 units every 8 hours) is recommended once the international normalised ration (INR) is below 1.5 and the platelet count is greater than 50 x 10 9 cells/L.…”
Section: Post Liver Transplantationmentioning
confidence: 92%